Impairment in object-in-place scene learning after uncinate fascicle section in macaque monkeys. - Browning, P; Gaffan, D (2008)
Three previous experiments have shown that a disconnection of frontal cortex from inferior temporal cortex in monkeys impairs a variety of visual learning tasks but leaves concurrent object discrimination learning intact. In the present experiment, three monkeys were trained on an object-in-place task where concurrent object discrimination learning took place within unique background scenes. After surgery to transect the uncinate fascicle, the monosynaptic route between prefrontal cortex and inferior temporal cortex, all three monkeys showed an impairment relative to their preoperative performance. Combined with previously reported impairments after uncinate fascicle transection, the interaction between frontal cortex and inferotemporal cortex is likely to be important in discrimination learning in background scenes because learning depends on associating the visual elements of a scene together with the appropriate choice object. This result adds to recent evidence showing that tasks such as object-in-place learning and conditional learning are impaired after disconnection of frontal cortex from inferior temporal cortex because those tasks require the representation of temporally extended events.